Versatile spider venom peptides and their medical and agricultural applications. (February 2019) - Saez, Natalie J.; Herzig, Volker
Abstract: Spiders have been evolving complex and diverse repertoires of peptides in their venoms with vast pharmacological activities for more than 300 million years. Spiders use their venoms for prey capture and defense, hence they contain peptides that target both prey (mainly arthropods) and predators (other arthropods or vertebrates). This includes peptides that potently and selectively modulate a range of targets such as ion channels, receptors and signaling pathways involved in physiological processes. The contribution of these targets in particular disease pathophysiologies makes spider venoms a valuable source of peptides with potential therapeutic use. In addition, peptides with insecticidal activities, used for prey capture, can be exploited for the development of novel bioinsecticides for agricultural use. Although we have already reviewed potential applications of spider venom peptides as therapeutics (in 2010) and as bioinsecticides (in 2012), a considerable number of research articles on both topics have been published since, warranting an updated review. Here we explore the most recent research on the use of spider venom peptides for both medical and agricultural applications. Graphical abstract: Highlights: Spider venoms contain a huge diversity of potent and target-selective peptides with a correspondingly vast array of pharmacological activities. Their potential medical applications have focused on the treatment of diseases such as stroke, cancer, pain and erectile dysfunction. They also have great potential for application in agriculture as environmentally benign bioinsecticides.